Kemampuan Berpikir Kreatif Siswa Sekolah Dasar pada Pembelajaran IPAS melalui Model CTL Berbantuan Video Interaktif - Astri Deswita; Rohana Rohana; Hendri Gunawan (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model assisted by interactive videos on students' creative thinking skills in the IPAS subject on the topic of the human respiratory system in Grade V at SD Negeri 90 Palembang in the 2024/2025 academic year. This research is a quantitative study using a Posttest-Only Control Group Design. The population consisted of all fifth-grade students at SD Negeri 90 Palembang, totaling 44 students. The entire population was used as the sample and was divided into two learning groups: the experimental class and the control class. The experimental class was taught using the Contextual Teaching and Learning model assisted by interactive videos, while the control class was taught using the Contextual Teaching and Learning model without video assistance. The instrument used was an essay test consisting of 10 items designed to assess creative thinking skills. The test items had previously undergone validation for validity, reliability, discriminating power, and difficulty level. The hypothesis was tested using an Independent Sample t-Test, after first conducting tests for normality and homogeneity. The results showed that the average creative thinking score in the experimental class was 81.23 (very good), which was higher than the control class average of 70.14 (good). The hypothesis test result showed that the t_calculated = 3.280 was greater than the t_table= 2.018 at a significance level of 0.05, indicating that the null hypothesis (Ho) was rejected. Thus, there is a significant effect of using the CTL model assisted by interactive videos on improving students’ creative thinking skills in IPAS learning.